Die uitnodiging na die nagmaal - Booysen, D. J. (Hervormde teologiese studies, 1989)
Invitation to Holy CommunionParticipation in Holy Communion raises a number of questions. The Church is compelled to see to it that the Sacrament is not desecrated and on the other hand, the Church is obliged to encourage participation. The problem arises when visitors of the same confession turn up at the celebration. Can they be allowed to participate? In some churches the answer is an undoubted: No. For other churches it is self-evident - there are not obstacles. In between are a number of churches who are more hesitant and a number of safeguards are adopted. In this case - as is the case in the Nederduitsch Hervormde Kerk - the responsibility rests mainly with the participant, as he must be aware of the preconditions set by the church and whether he can honestly declare that as far as he is concerned he is unaware of anything prohibiting him from participation. Thus no changes in the church statute are required.